Effects of intraventricular methotrexate administration on Cuprizone-induced demyelination in mice - Mueller, Andre M.; Nassery, Adam; Conlon, Hana; Liu, Xinhe; Cristofanilli, Massimiliano; Jun, Esther; Yoon, Bo Hyung; Sadiq, Saud A. (Frontiers in Molecular Neuroscience, 2013)
We previously showed that intrathecal administration of methotrexate slowed disability progression in multiple sclerosis patients with progressive disease. In general MS patients with progressive disease respond poorly to anti-inflammatory therapies. In order to better understand the mechanism by which methotrexate is protective in progressive MS, we analyzed its impact on the non-inflammatory cuprizone-induced demyelination model. When low-dose methotrexate was administered intracerebroventricularly it reduced demyelination and accumulation of GFAP+ reactive astrocytes in the corpus callosum. Administration of methotrexate after the withdrawal of cuprizone neither delayed remyelination nor influenced the number of astrocytes in the corpus callosum suggesting that methotrexate does not interfere with repair processes in the CNS. Moreover, methotrexate increased the expression of IGF1 in vitro and in vivo, a factor known to protect oligodendrocytes and limit the activation of astrocytes. Our studies show that methotrexate has an impact on pathogenic process in a demyelination model whose pathophysiological basis is not primarily related to inflammatory mechanisms, similar to neurodegenerative mechanisms associated with progressive MS. The pronounced inhibitory influence of methotrexate on the accumulation of astrocytes in the corpus callosum suggests that intrathecal methotrexate modulates astroglial activation in progressive MS possibly by promoting CNS production of IGF1.